1978
DOI: 10.1007/bf00310336
|View full text |Cite
|
Sign up to set email alerts
|

The modifying effect of multiple generation selection and dietary cadmium on methyl mercury toxicity in Japanese quail

Abstract: Japanese quails were exposed to dietary methyl mercury chloride in graded amounts from 2--8 ppm through a series of multiple-generation experiments with the experimental periods lasting from 6--12 weeks, starting with the experimental diets when the birds were 6 weeks old. Cadmium chloride was added to diets with and without mercury and fed to groups in three of the five experiments. Hatchability was depressed at 8 ppm mercury. The mortality of chicks from 8 ppm exposed parents was 100% in the first two genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…However, reproductive responses were generally similar between the first and second generations, and we judged that the uncertainty of including the second‐generation results was less than the uncertainty of conducting the regression analysis with 50% fewer data points. An additional Japanese quail study provides results that are generally consistent with those of Eskeland and Nafstad , but it could not be included in the regression analysis because the control results were not sufficiently comparable.…”
Section: Literature Review Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, reproductive responses were generally similar between the first and second generations, and we judged that the uncertainty of including the second‐generation results was less than the uncertainty of conducting the regression analysis with 50% fewer data points. An additional Japanese quail study provides results that are generally consistent with those of Eskeland and Nafstad , but it could not be included in the regression analysis because the control results were not sufficiently comparable.…”
Section: Literature Review Resultsmentioning
confidence: 93%
“…Species represented by more than 1 study include ring-necked pheasant (Phasianus colchicus), Japanese quail (Coturnix japonica), and mallard (Anas platyrhynchos). Three or more exposure groups were tested for 5 of the species, including American kestrels (Falco sparverius) [24], zebra finches (Taeniopygia guttata) [85], ring-necked pheasants [25], Japanese quail [86,87], and mallards [10,77,[88][89][90][91][92]. Dose-response relationships are shown on a dietary Hg basis in Figures 1 and 2 Tables S2 through S6.…”
Section: Literature Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results presented here differ from those of Tejning (1967), who stated that elimination of mercury with excrement in domestic fowl accounted for approximately 12% of the mercury intake. Eskerland and Nafstad (1978), however, reported a daily excretion rate of 11-21% of the mercury intake in poultry. It appears that, with levels of mercury low enough not to cause poisoning, a single dose of mercury can be excreted in the faeces and therefore may not be a major environmental hazard at low levels.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological effect of the destruction of the littoral cells is discussed.This study is part of a series of investigations showing the effect of methylmercury on quail. Atomic absorption spectroscopical studies showing the effect of accumulation of mercury, transfer to eggs and the resulting effect on hatchability and chick mortality followed through multiple generations are presented in two other papers Eskeland & Nafstad 1978). These AAS-studies clearly showed that the mercury concentration in the liver, kidney and brain was higher in cocks than in hens.…”
mentioning
confidence: 98%